Character Formation and Moral Development in Children Through Mosque Engagement Programs - Hikmawati, Hanifah; Asyhari, Yasin (Communautaire: Journal of Community Service, 2024)
The formation of akhlakul karimah (noble character) is an important aspect of children's education in Islamic teachings, which includes good moral and ethical values. This study is based on the aim to explore the effectiveness of mosque-centered activities in fostering these values among children. The background of this study highlights the important role of mosques in guiding children towards good morals through various religious activities. The methodology of this paper is based on Participatory Action Research (PAR) which involves active collaboration with community members in the planning, implementation, and evaluation of the program. This approach includes counseling and training on akhlakul karimah values, organizing religious activities such as calligraphy, hadrah, qiro'ah, and Qur'an reading, increasing parental and community involvement, and conducting ongoing evaluations to assess the impact of the program. The findings of the study revealed that the mosque-centered approach plays an effective role in fostering positive attitudes and behaviors among children. Mosque-centered activities can also provide a positive impression to the community about the importance of prospering the mosque. The results of this study are expected to provide an understanding of how religious institutions such as mosques can play an important role in the moral and ethical development of children through community involvement and active participation.